An Advanced Multicarrier Residential Energy Hub System Based on Mixed Integer Linear Programming - Yue Yuan; Angel A. Bayod-Rújula; Huanxin Chen; Amaya Martínez-Gracia; Jiangyu Wang; Anna Pinnarelli (International Journal of Photoenergy)
This work proposes a multicarrier energy hub system with the objective of minimizing the economy cost and the CO2 emissions of a residential building without sacrificing the household comfort and increasing the exploitation of renewable energy in daily life. The energy hub combines the electrical grid and natural gas network, a gas boiler, a heat pump, a photovoltaic plant, and a photovoltaic/thermal (PV/T) system. In addition, to increase the overall performance of the system, a battery-based energy storage system is integrated. To evaluate the optimal capacity of each energy hub component, an optimization scheduling process and the optimization problem have been solved with the YALMIP platform in the MATLAB environment. The result showed that this advanced system not only can decrease the economic cost and CO2 emissions but also reduce the impact to electrical grid.